2022
DOI: 10.3390/jcm11133673
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): Insights for the Practicing Clinician

Abstract: Following the discovery of the Lipoprotein(a) (Lp(a)) molecule by Kare Berg in 1963, many physiological and pathological properties of this particle remain to be fully understood. Multiple population-based studies have demonstrated a correlation between elevated Lp(a) levels and the incidence of cardiovascular disease. Data extrapolated from the Copenhagen City Heart and ASTRONOMER studies also demonstrated the link between Lp(a) levels and the incidence and rate of progression of calcific aortic stenosis. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…Conversely, previous studies indicated an inverse relationship (the higher the Lp(a) level the lower the risk of AF incidence) [30][31][32]. Two extensive, Danish cohort studies (the Copenhagen City Heart Study and the Copenhagen General Population Study) lasting 20 years (77,000 patients) confirmed the enhanced danger of aortic valve stenosis (AVS) among individuals that presented higher Lp(a) values (three-fold elevated danger when concentration >90 mg/dL) [33]. AVS progression as well as the necessity of a previous reaction in those with increased lipoprotein(a) level was also acknowledged in post hoc analysis of the Astronomer trial [34].…”
Section: Group Of Patients Outcome Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, previous studies indicated an inverse relationship (the higher the Lp(a) level the lower the risk of AF incidence) [30][31][32]. Two extensive, Danish cohort studies (the Copenhagen City Heart Study and the Copenhagen General Population Study) lasting 20 years (77,000 patients) confirmed the enhanced danger of aortic valve stenosis (AVS) among individuals that presented higher Lp(a) values (three-fold elevated danger when concentration >90 mg/dL) [33]. AVS progression as well as the necessity of a previous reaction in those with increased lipoprotein(a) level was also acknowledged in post hoc analysis of the Astronomer trial [34].…”
Section: Group Of Patients Outcome Implicationsmentioning
confidence: 93%
“…The unique structure of the Lp(a) particle implicates complications with the accuracy of its measurement. Many repetitive KIV repeats in apo(a) determine Lp(a) size heterogeneity which makes the standardization very challenging [33]. The main aspects of Lp(a) measurement concern the isoform-sensitivity of measurement systems, assay calibrators, and the type of antibodies used for the measurement [58].…”
Section: Measurement Of Lipoprotein(a) Cut-off Values and Risk Strati...mentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящий момент интенсивно изучается роль частицы Лп(а), связанной дисульфидной связью с апоВ. Липидный состав Лп(а) из-за связи с апоВ напоминает ЛНП, и дополнительно в нем присутствует еще один белковый домен -аполипопротеин А, большой гидрофильный белок, напоминающий по структуре молекулу плазминогена [32]. Популяционные исследования показали, что содержание Лп(а) не зависит от пола и возраста, наличия диабета, курения, артериальной гипертензии и влияния других заболеваний, но наследуется с высокой вероятностью и остается неизменным в течение жизни [32].…”
Section: материал и методыunclassified
“…Многочисленные исследования показали, что повышенные уровни Лп(а) ассоциированы с ранним развитием атеросклероза и преждевременных ССЗ [32][33][34][35]. Так, в исследовании Лп(а) у пациентов с ранней манифестацией ОКС повышенные концентрации частицы выявлялись в 41% случаев по сравнению с 14% в контрольной группе, уровень >30 мг/дл был независимо связан с развитием ОКС, а уровень Лп(а) выше 15 мг/дл ассоциировался с поражением коронарных артерий из разных бассейнов [35].…”
Section: материал и методыunclassified